2007
DOI: 10.1111/j.1467-6427.2007.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Keeping company with hope and despair: family therapists' reflections and experience of working with childhood depression

Abstract: The BIOMED international outcome study on childhood depression offered a unique opportunity for the systematic treatment of children and families with major depression using systemic psychotherapy. This paper describes the experiences of clinicians working with the families referred and the theoretical and clinical models that evolved during the treatment process. The concept of 'keeping company with hope and despair' emerged as an overarching framework for thinking about the quality of the therapeutic relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…The trial was implemented in three clinical settings in Europe: the Tavistock Clinic, London, the Aghia Sophia Children's Hospital, Athens and the Hospital for Children and Adolescents, Helsinki. Previously reported results that both FIPP and SIFT resulted in a marked and sustained improvement in children's depression (see Trowell et al, 2007 for a more detailed description of the project and outcome and Pentecost and McNab, 2007 for experiences of clinicians working with the families and the theoretical and clinical models that evolved during the treatment process). In the present study we explored the significance of family functioning, as assessed by mothers and family therapists, as an element of therapeutic change in youth depression in individual and family therapy.…”
mentioning
confidence: 99%
“…The trial was implemented in three clinical settings in Europe: the Tavistock Clinic, London, the Aghia Sophia Children's Hospital, Athens and the Hospital for Children and Adolescents, Helsinki. Previously reported results that both FIPP and SIFT resulted in a marked and sustained improvement in children's depression (see Trowell et al, 2007 for a more detailed description of the project and outcome and Pentecost and McNab, 2007 for experiences of clinicians working with the families and the theoretical and clinical models that evolved during the treatment process). In the present study we explored the significance of family functioning, as assessed by mothers and family therapists, as an element of therapeutic change in youth depression in individual and family therapy.…”
mentioning
confidence: 99%
“…Pruitt (2007) gave an overview of structural, interpersonal and attachment-based family therapy for depression in adolescent boys and concluded that there was some evidence for the effectiveness of each of these approaches to treatment. Pentecost and McNab (2007) described how the concept of 'keeping company with hope and despair' emerged as an overarching framework for thinking about the quality of the therapeutic relationship when working with depressed young people and their families within the context of a controlled trial (which is mentioned below in the section on research (Trowell et al, 2007)). On a similar theme, Flaskas (2007) explored the dynamics of hope and hopelessness within intimate relationships, and their embeddedness in wider social and historical processes.…”
mentioning
confidence: 99%
“…Παρόλα αυτά επισημαίνεται ότι η κατάθλιψη στα παιδιά, πολλές φορές παραμένει αδιάγνωστη (Son & Kirchner, 2000). Σ' αυτό συμβάλλει η ανάγκη του ενήλικα να πιστεύει στην ελπίδα και την υπόσχεση της παιδικής ηλικίας, που τον εμποδίζει να αποδεχθεί τα συμπτώματα απελπισίας και κατάθλιψης σ' ένα παιδί (Pentecost & Mc Nab, 2007). Ως εκ τούτου καθίσταται σημαντική η πρόωρη διάγνωση και αντιμετώπιση της διαταραχής, γιατί δίνουν τη δυνατότητα για σχεδιασμό αποτελεσματικότερων παρεμβάσεων πρόληψης στην παιδική ηλικία, αποφεύγοντας έτσι την εμφάνιση χρόνιας ψυχοπαθολογίας στην ενήλικη ζωή (Maughan, Collishaw & Stringaris, 2013).…”
Section: η έννοια της κατάθλιψης στην παιδική ηλικίαunclassified